2017
DOI: 10.1051/0004-6361/201629679
|View full text |Cite
|
Sign up to set email alerts
|

A new insight into the Galactic potential: A simple secular model for the evolution of binary systems in the solar neighbourhood

Abstract: Context. Among the main effects that the Milky Way exerts in binary systems, the Galactic tide is the only one that is not probabilistic and can be deduced from a potential. Therefore, it is possible to perform an analysis of the global structure of the phase space of binary systems in the solar neighbourhood using the Galactic potential. Aims. The aim of this work is to obtain a simple model to study the collisionless dynamical evolution of generic wide binaries systems in the solar neighbourhood. Methods. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It is important that the orbital elements are defined with respect to a reference frame with axis directions fixed in time (cf. Brasser 2001;Veras & Evans 2013a;Correa-Otto et al 2017). In the limit of the cluster tide going to zero these orbital elements stay constant.…”
Section: Orbital Elements and Delaunay Variablesmentioning
confidence: 99%
“…It is important that the orbital elements are defined with respect to a reference frame with axis directions fixed in time (cf. Brasser 2001;Veras & Evans 2013a;Correa-Otto et al 2017). In the limit of the cluster tide going to zero these orbital elements stay constant.…”
Section: Orbital Elements and Delaunay Variablesmentioning
confidence: 99%
“…Here we follow the simplified model of Heisler & Tremaine (1986), taking into account only the leading term of the vertical tide, neglecting perturbations on other directions (which are about ∼ 15 times smaller, Heisler & Tremaine 1986). Various studies looked on the additional terms (e.g Veras & Evans 2013;Correa-Otto et al 2017) and found the behaviour to be qualitatively similar to Heisler & Tremaine (1986).…”
Section: Galactic Tidesmentioning
confidence: 99%
“…Secular evolution of stellar-binaries could also occur due to perturbation by external non-stellar potentials, such as binaries perturbed by a massive black hole in galactic nuclei (Antonini & Perets 2012;Prodan et al 2015); binaries in cluster potentials (Hamilton & Rafikov 2019a, or wide binaries perturbed by the Galactic tidal field (Correa-Otto et al 2017). In fact, already decades ago the secular evolution of Oort cloud objects due to the Galactic tidal field was shown to be important for the production of highly eccentric comets and the formation of long-period and sun-grazing comets (e.g Heisler & Tremaine 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Their wide physical separations mean that they have weak binding energy -the orbits can easily be disrupted, hence they are assumed to be coeval and have evolved independently. A large sample of such binaries can be used to probe the Galactic gravitational potential (Chanamé & Gould 2004;Quinn & Smith 2009;Monroy-Rodríguez & Allen 2014;Correa-Otto et al 2017). CPM systems containing a white dwarf and a burning star provide the advantage that the age of the system can be estimated from white dwarf cooling, while the progenitor chemistry and the radial velocity of the system can be extracted from the co-moving counterpart.…”
Section: Introductionmentioning
confidence: 99%